2000
DOI: 10.1016/s0002-9440(10)65007-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Angiogenesis and Vascular Tumor Growth by Interferon-Producing Cells

Abstract: We developed an in vivo gene therapy approach to characterize and optimize the anti-angiogenic activity of class I interferons (IFNs), using packaging cell lines producing an amphotropic LXSN-based retrovirus expressing either IFN-alpha1 (alpha1Am12), IFN-beta (betaAm12) murine cDNAs, or the vector alone (neoAm12). Pretreatment of endothelial-like Eahy926 cells in vitro with conditioned media (CM) from alpha1Am12 or betaAm12 cells for 48 hours significantly inhibited their migration and invasion as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 33 publications
3
81
0
Order By: Relevance
“…These findings support the hypothesis that the antiangiogenic effect of IFN-g on human endothelial cells required other mechanisms besides apoptosis. Human IFN-g inhibits endothelial migration and proliferation (Brouty-Boye and Zetter, 1980;Friesel et al, 1987;Tsuruoka et al, 1988;Albini et al, 2000) and has strong antiproliferative effects on NB tumour cells (Ponzoni et al, 1992;Airoldi et al, 2004), from which the human endothelial cells derived. Thus, the antiangiogenic effect was likely due to a combination of apoptosis and reduced proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the hypothesis that the antiangiogenic effect of IFN-g on human endothelial cells required other mechanisms besides apoptosis. Human IFN-g inhibits endothelial migration and proliferation (Brouty-Boye and Zetter, 1980;Friesel et al, 1987;Tsuruoka et al, 1988;Albini et al, 2000) and has strong antiproliferative effects on NB tumour cells (Ponzoni et al, 1992;Airoldi et al, 2004), from which the human endothelial cells derived. Thus, the antiangiogenic effect was likely due to a combination of apoptosis and reduced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Precisely, murine IFN-g produced by either CD4 þ or CD8 þ cells inhibits tumour-induced angiogenesis in syngeneic tumour models (Saiki et al, 1992;Qin and Blankenstein, 2000;Blankenstein and Qin, 2003). Human IFN-g inhibits proliferation and migration of human endothelial cells and capillary tube formation in vitro (BroutyBoye and Zetter, 1980;Friesel et al, 1987;Tsuruoka et al, 1988;Maheshwari et al, 1991;Albini et al, 2000) and represses lymphocyte-induced tumour angiogenesis (Sidky and Borden, 1987).…”
mentioning
confidence: 99%
“…3A). Because it has been demonstrated that IFNs inhibit endothelial cell migration across the basal lamina propria [4,5], we tested the effect of IFI16 expression on VEGF and bFGF-induced invasion (transmigration) of a reconstituted basal lamina in modified Boyden chambers. In this assay [35,36], cells transmigrate from an upper well through a porous filter coated with Matrigel toward chemoattractants (i.e.…”
Section: Inhibition Of Huvec Chemotaxis Invasion and Tube Morphogenmentioning
confidence: 99%
“…Anti-angiogenic therapy uses negative neovascularization regulators to suppress pro-angiogenic signals or increase inhibitory signals [3]. IFNs, along with their role in viral interference and cell proliferation, possess potent antiangiogenic activity [4][5][6]. They down-regulate the expression of several proangiogenic molecules, such as bFGF [7], matrix metalloproteases (MMP-2 and MMP-9) [8][9][10], and IL-8 [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that IFN-b has many biological effects. 42,43 IFN-b exhibits antitumor effects via various mechanisms, such as upregulation of MHC class I, 44 activation of macrophages and NK cells, 45 downregulation of angiogenic agents 46 and inhibition of tumor cell proliferation. 47 It is likely that inhibition of tumor cell proliferation by IFN-b is one of the most important mechanisms in our study, because the cell growth inhibitory effect of IFN-b was often higher than that of IFN-a and g 47,48 and, in fact, the in vitro growth of CT-26 cells was efficiently inhibited by IFN-b.…”
Section: Discussionmentioning
confidence: 99%